DETERMINAN KEPUTUSAN PEMBELIAN SAYURAN HIDROPONIK: PERAN FAKTOR PRIBADI DAN PSIKOLOGIS DI KECAMATAN BREBES - Titin Nur Laela; Khusnul Khotimah; M Erwin Dwi Lisyanto; Suci Nur Utami; Muhammad Dini Adita (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2026)
The increasing public awareness of healthy lifestyles has driven the demand for hydroponic vegetables as a hygienic and high-quality food alternative. This study aims to analyze the influence of cultural, social, personal, and psychological factors on purchasing decisions of hydroponic vegetables in Brebes District. The research employed a descriptive quantitative approach using multiple linear regression analysis. Data were collected through questionnaires distributed to 100 respondents selected using simple random sampling. The partial test results indicate that personal and psychological factors have a significant effect on purchasing decisions, with significance values of 0.000 (<0.05). The personal factor shows the strongest influence with a regression coefficient of 0.253, followed by the psychological factor at 0.252. Meanwhile, cultural and social factors do not have a significant effect, with significance values of 0.650 and 0.663 (>0.05), respectively. Simultaneous testing reveals that all independent variables jointly have a significant effect on purchasing decisions, with an F-value of 48.276 and a significance level of 0.000.